Efficient broadband linear polarization conversion metasurface based on %‐shape. Issue 1 (22nd August 2019) - Long, Fei; Yu, Shixing; Kou, Na; Zhang, Can; Ding, Zhao; Zhang, Zhengping
Abstract: In this work, a high‐efficiency polarization conversion metasurface (MTS) is introduced, which has the ability to convert a linear polarization state to its orthogonal one. The proposed MTS of the unit cell is composed of cut‐rod and two unequal disks (like %‐shape), which can achieve cross‐polarized waves for both x ‐ and y ‐polarized normal incident waves. The electric and magnetic responses of this structure generate three plasmon resonances, which lead to the bandwidth extension of polarization rotation. The numerical simulations use the finite element method. It has been demonstrated that the polarization conversion ratio (PCR) is more than 0.95 from 8.85 GHz to 18.85 GHz. The maximum PCR is even nearly 1 at the three plasmon resonance frequencies. A prototype with an overall size of 9.13 λ 0 × 9.13 λ 0 × 0.11 λ 0 (where λ 0 is the free‐space wavelength at the center frequency of the operating bandwidth) has been fabricated and measured. The experimental results agree well with the numerical ones, and validate broadband cross‐polarization reflections' performance of the proposed structure.